FACILITATING EFL STUDENTS’ LEARNING GRAMMAR; A DESIGN GAME BASED LEARNING - Maliqul Hafis; Muhammad Iqbal Ripo Putra; Sahrawi . (Institut Pendidikan Tapanuli Selatan, 2020)
For second and foreign language mastery, grammar instruction’s role is inevitably essential. Unfortunately, some English teachers still teach grammar deductively in foreign language contexts, such as in Indonesia. Students are giving grammar rules and examples, told to memorize them, and then asked to apply the rules to other examples. This particular teaching approach believes in generating learners who can not express the language even if they have extensive grammar laws. The approach seeks to contribute to the passive participation of learners and negative grammar-learning feelings. This paper aims to provide an alternative solution to this problem by facilitating a teaching aid of game-based activities. Research and development had taken to develop teaching media. The study also administered questionnaires for collecting the data. The study involved 53 Islamic boarding school students taking an English course. The findings indicated that the teaching aid was successful in creating more attractiveness and non-threatening grammar class, changing students' negative perceptions of grammar learning, and improving their perceived communication skills. The products developed by researchers are suitable for use as a learning aid.